Kajian Olahraga Boxing Perspektif Hadits, Kesehatan, dan Maqāṣid al-Syarī‘ah - Syaghaf M. Sa'ad; Nasrulloh (Al-Kindi, 2026)
This article analyzes boxing from the perspectives of health, hadith, and Maqāṣid al-Sharīʿah through a qualitative-normative approach using library research. The study departs from the empirical reality that boxing, as a high-contact sport, carries serious risks such as concussions, recurrent head injuries, and potential neurological impairments, which contradict Islamic principles on the preservation of life and the prohibition of harming oneself or others. In contrast, scholarly ideality requires that sports be practiced with due regard to safety, health, and ethical values; however, previous research has rarely connected boxing with hadith analysis and maqāṣid al-sharīʿah, creating a significant research gap. This article discusses three main dimensions: first, an evaluation of the health implications of boxing and their relevance to Islamic legal principles; second, an analysis of hadiths concerning the prohibition of harm (lā ḍarar wa lā ḍirār) as an ethical foundation for assessing boxing-related risks; and third, an appraisal of boxing through the framework of maqāṣid al-sharīʿah, particularly the objectives of preserving life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), and balancing benefits and harms (maṣlaḥah–mafsadah). The findings indicate that although boxing offers fitness benefits, it presents substantial health risks, necessitating strict evaluation according to Islamic principles such as modifying training formats, eliminating dangerous head strikes, enforcing maximum protective measures, or avoiding high-risk competitive forms. Thus, boxing can only be deemed acceptable within certain limits, insofar as it aligns with the maqāṣid al-sharīʿah and Islamic ethical principles that prioritize safety above all. Keywords:  Boxing, Health, Hadith, Maqāṣid al-Sharīʿah, Sports Ethics